'Is that okay, teacher?' The camera as a tool to challenge power relations in a participatory action research classroom. (October 2021) - Hemy, Avy Dwight; Meshulam, Assaf
Conducting a participatory action research (PAR) in schools is challenged by traditional asymmetrical power relations between adult teacher-researcher and young student-participants inherent in the school setting. In this article, we present PowerView, a new method that may reduce power hierarchy in the research classroom. Based on postcolonial theory, feminist theories, and critical visual studies, we implemented the idea of 'reversal-of-the-gaze' by asking the student-participants in our PAR program to turn their cameras at the instructor-researcher and capture images that represent their point of view of him. Enabling the students' to gaze back at the instructor-researcher/serial observer with their cameras disrupted the hierarchical power paradigm in the research classroom and created a more equal space. The article will introduce the methodological stages of PowerView and present findings that demonstrate the potential of the method to change power relations between the researcher and students and challenge the power structure at the research classroom.